2012
DOI: 10.1097/aog.0b013e318259565a
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Failure Rates of Etonogestrel Subdermal Implants in Overweight and Obese Women

Abstract: Objective To estimate the contraceptive failure rates of the etonogestrel subdermal contraceptive implant in overweight and obese women, and compare failure rates to women of normal weight and women using intrauterine devices (IUDs). Methods The Contraceptive CHOICE Project is a large prospective cohort study designed to promote the use of long-acting reversible contraceptive methods to reduce unintended pregnancies in the St. Louis region. Participants are provided reversible contraception of their choice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(52 citation statements)
references
References 19 publications
(20 reference statements)
2
42
0
8
Order By: Relevance
“…A cohort study with 1168 etonogestrel implant users showed that the effectiveness of the implant did not decrease in overweight or obese women [17]. A recent pharmacokinetic study also demonstrated no significant differences in etonogestrel concentrations between normal-weight and obese women over time, consistent with the clinical effectiveness data [18].…”
Section: Discussionsupporting
confidence: 65%
“…A cohort study with 1168 etonogestrel implant users showed that the effectiveness of the implant did not decrease in overweight or obese women [17]. A recent pharmacokinetic study also demonstrated no significant differences in etonogestrel concentrations between normal-weight and obese women over time, consistent with the clinical effectiveness data [18].…”
Section: Discussionsupporting
confidence: 65%
“…58 Systematic reviews and large cohort studies have revealed no or mixed effects for the effect of both body weight and BMI on COCs, IUDs, implants, and contraceptive injections. [238][239][240] When examining complications, the World Health Organization and CDC found that among adult women, COC users with obesity are more likely than nonusers to experience thromboembolic complications. 111 However, the absolute risk of thromboembolic complications among adolescent COC users is low.…”
Section: Adolescents With Disabilitiesmentioning
confidence: 99%
“…117,118 The World Health Organization and CDC report that data are limited and inconsistent about whether COC effectiveness varies by body weight or BMI. 37,[150][151][152] A common concern of both adolescents and providers is additional weight gain among adolescents with obesity after they start contraception. Data suggest that women with obesity are no more likely to gain weight with COCs, the vaginal ring, IUDs, or implants than normalweight peers.…”
Section: Adolescents With Obesitymentioning
confidence: 99%